1993
DOI: 10.2337/diacare.16.10.1387
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Glucose, Lipid Metabolism, and Reduces Blood Pressure in Hypertensive, Obese Women

Abstract: These findings suggest that metformin treatment in obese, nondiabetic, hypertensive women produces a more favorable cardiovascular risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
101
3
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(115 citation statements)
references
References 0 publications
8
101
3
3
Order By: Relevance
“…Thus, we were neither able to support nor rule out the previously suggested beneficial effect of metformin on BP in insulin-resistant hypertensives [6] or obese female subjects [7].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Thus, we were neither able to support nor rule out the previously suggested beneficial effect of metformin on BP in insulin-resistant hypertensives [6] or obese female subjects [7].…”
Section: Discussioncontrasting
confidence: 95%
“…An effect related to hyperinsulinaemia is supported by a study of spontaneously hypertensive rats [13]. The present study population had higher diastolic and systolic BP at baseline compared to the study of Giugliano et al [7]. We found only a minor (5 mmHg) but significant decline in diastolic office blood pressure within the group of metformin-treated patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Why? One could speculate it reflects the known CV benefits of metformin over sulfonylureas, less weight gain and lowered triglyceride levels (8,9), and the resulting effects on potential CV pathogenic mechanisms such as plasminogen activator inhibitor-1 (10). To be valid, it needs to be shown that CV-related mortality was in fact low-ered.…”
mentioning
confidence: 99%
“…This also seems to contradict the hypothesis of a direct relationship between insulin sensitivity and blood pressure level. [18][19][20][21] We have earlier demonstrated that in spite of an impaired insulin-stimulated glucose uptake the insulin-induced tubular sodium reabsorption is retained in relatives. 12 The suppression of plasma aldosterone observed in controls during the clamp was blunted in relatives, which could suggest a tendency to sodium retention in these subjects.…”
Section: Discussionmentioning
confidence: 99%